2022
DOI: 10.1007/s00167-022-07222-w
|View full text |Cite
|
Sign up to set email alerts
|

MPFL repair after acute first-time patellar dislocation results in lower redislocation rates and less knee pain compared to rehabilitation: a systematic review and meta-analysis

Abstract: PurposeThis study aimed to explore the efficacy of medial patellofemoral ligament (MPFL) repair versus nonoperative rehabilitation treatment on the rate of patellar redislocation and functional outcomes in skeletally mature patients with traumatic, first‐time patellar dislocations. Materials and methodsMEDLINE, PubMed and EMBASE were searched from database inception to May 2022 for studies examining the management options for acute first‐time patellar dislocations. This study was conducted in accordance with P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 67 publications
(81 reference statements)
0
6
0
Order By: Relevance
“…Each article's levels of evidence (LoE) was recorded using the Oxford Centre for Evidence-Based Medicine criteria [18]. The methodological quality of the studies included was evaluated through the methodological index for non-randomized studies (MINORS) criteria [19][20][21]. The MINORS score ranges from 0 to 18 for non-comparative studies and 0 to 24 for comparative studies, with a higher score reflecting higher quality.…”
Section: Methodological Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Each article's levels of evidence (LoE) was recorded using the Oxford Centre for Evidence-Based Medicine criteria [18]. The methodological quality of the studies included was evaluated through the methodological index for non-randomized studies (MINORS) criteria [19][20][21]. The MINORS score ranges from 0 to 18 for non-comparative studies and 0 to 24 for comparative studies, with a higher score reflecting higher quality.…”
Section: Methodological Quality Assessmentmentioning
confidence: 99%
“…The mean follow-up was 57.6 ± 31.8 months. Seventeen studies [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][34][35][36][37][38][39] reported sex data, and 43.3% were men, and 56.7% were women. The demographic data of the included studies are listed in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…if trial is negative, were confidence intervals [CIs] calculated or post‐hoc power calculations performed?). The maximum score for trials with positive and negative findings is 20 and 21 points, respectively [34].…”
Section: Methodsmentioning
confidence: 99%
“…82 A recent systematic review and meta-analysis found lower rates of redislocation and knee pain in first-time patellar dislocators treated with surgery compared with nonoperative management. 83 It is worth noting that despite reducing the rate of patellar dislocation, surgical interventions for PI have been associated with increased rates of complications including patellofemoral arthritis in some studies. 84 This highlights the complexity of managing patellofemoral disorders and underscores the importance of individualized treatment plans tailored to each patient's unique circumstances and needs.…”
Section: Treatment Of Patellofemoral Injuries In Soccermentioning
confidence: 99%